ANALISIS RAGAM BENTUK DAN APLIKASI MASHDAR SHARĪH DALAM KITAB AKHLAQUL LIL BANIN JUZ 1 (ANALISIS MORFOSINTAKSIS) - Irfan Adi Pamungkas; Akbar Syamsul Arifin (Universitas Negeri Semarang, 2023)
Research related to this neologism aims to describe the novelty of Arabic vocabulary in the barrel of the document. The data obtained is a collection of articles related to medical barrels found on the aljazeera.net website. The method used in this study is the descriptive analysis method. This study, used three steps to analyze the Arabic neologism of medical scale, identification, definition, and classification. From the analysis conducted, it was found that the Arabic neologisms of the medical barrel are divided into three kinds, (1) patterned derivations انفعال /infiʕa:l/, فَعَل /faʕal/, افتعال /iftiʕal/, استفعال /istifʕa:l/, فعولة /faʕu:lah/, أفعال /afʕa:l/, فعل atau فعل /faʕlun/ atau /fiʕlun/, تَفَعُّل /tafaʕʕul/, تفعيل /tafʕi:l/, فعالة /fiʕa:lah/, فعلان /faʕla:n/, dan فعال /fuʕa:l/. Kemudian اسم فاعل /ismul fa:ʕil/, اسم اللآلة /ismul a:lat/, اسم المكان /ismul maka:n/, فَعَّال /faʕʕa:l/, فَعَّالة /faʕʕalah/, dan نسبة /nisbah/; (2) Semantic relations divided into old word use and word translation; and (3) Word lending differentiated into loan word, loan blend, and loan shift.